2016
DOI: 10.1111/ejss.12342
|View full text |Cite
|
Sign up to set email alerts
|

Role of cationic polarization in humus‐increased soil aggregate stability

Abstract: It is well known that humus markedly increases soil aggregate stability, but at the same time strongly decreases the flocculation of clay particles in suspension. These seemingly inconsistent observations suggest the need for a deeper understanding of the physical mechanisms that govern clay–humus interactions. In this research, soil samples from an Entisol were used to explore the role of cationic polarization in humus‐increased soil aggregate stability and sodium (Na+) and potassium (K+) ions were used to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Soil internal forces, including electrostatic, surface hydration and van der Waals forces, have been proven to be the original driving forces that induce aggregate breakdown in water systems (Xu, Yu, & Li, 2015; Hu et al, 2015, 2018; Yu, Zhang, Zhang, Xin, & Li, 2017, 2020). The electrostatic repulsive force and surface hydration repulsive force cause the aggregate to disassemble, whereas the van der Waals attractive force promotes the stability of the aggregate (Huang, Li, Li, Xiong, & Jiang, 2016; Rengasamy, Tavakkoli, & McDonald, 2016). Generally, these soil internal forces can reach as high as 100–1,000 atm between two adjacent soil particles as rain enters into the dry aggregates (Hu et al, 2015; Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil internal forces, including electrostatic, surface hydration and van der Waals forces, have been proven to be the original driving forces that induce aggregate breakdown in water systems (Xu, Yu, & Li, 2015; Hu et al, 2015, 2018; Yu, Zhang, Zhang, Xin, & Li, 2017, 2020). The electrostatic repulsive force and surface hydration repulsive force cause the aggregate to disassemble, whereas the van der Waals attractive force promotes the stability of the aggregate (Huang, Li, Li, Xiong, & Jiang, 2016; Rengasamy, Tavakkoli, & McDonald, 2016). Generally, these soil internal forces can reach as high as 100–1,000 atm between two adjacent soil particles as rain enters into the dry aggregates (Hu et al, 2015; Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The earlier studies also found that a good linear relationship exists between the splash erosion rate and the mass percentage of fine particles with a diameter <20 μm released from macroaggregate breakdown according to results obtained by using the pipette method; however, that research did not consider the dynamics of various sized fractions of fragments with soil internal forces. Therefore, although the overall effects of soil internal forces on aggregate stability, splash erosion and their relations have been discussed by previous studies (Xu et al, 2015; Huang et al, 2016; Hu, Liu, Xu, Wang, et al, 2018; Yu et al, 2020), little work has been devoted to the exploration of the effects of soil internal forces on fragment size characteristics resulting from aggregate breakdown and their relationship with splash erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have shown that for clay systems, the electric eld-induced cation polarization could strongly inuence cation exchange in both equilibrium 20,37,38 and kinetics. 22,23,34 Taking the electric eld-induced cation polarization into account, the total potential energy of the mean force for adsorbed cations could be expressed as follows: 5,22,26 w(x) z gZFj(x) (15) where j(x) is the potential in the presence of the electric eldinduced cation polarization, and gZ is the apparent ionic charge number since all the non-coulombic interactions of the cation-clay can be attributed the coulombic interactions.…”
Section: Theoretical Analysis Of the Incomplete Ion-exchange State Inmentioning
confidence: 99%
“…Based on the Gouy-Chapman theory, some researchers have shown that the energy and state of cationic non-valence electrons could be fundamentally changed by such powerful external electric elds, 5 which could result in strong ion polarization and produce noncoulombic interactions between ions and the charged surfaces of clay. 26,27 Further studies have conclusively shown that the aforementioned ionic interface behavior can be enhanced with increases in ionic size. 28 Thereby, the newly discovered interaction forces probably play an essential role in the incomplete ion-exchange state of cation adsorption, and dominate the possible specic ion effects.…”
Section: Introductionmentioning
confidence: 95%
“…The above discussion showed that, under given boundary and initial conditions, aggregate stability determined soil water transport. On the other hand, previous studies have shown that soil particle interaction forces in an aggregate determined aggregate stability (Xu et al, 2015;Hu et al, 2015bHu et al, , 2018Huang et al, 2016). To improve understanding of the fundamental physics of soil water transport, we consider the effect of soil particle interaction forces on water transport for the two soils.…”
Section: The Relation Between Soil Particle Interaction Forces and Wamentioning
confidence: 99%